A zwitterionic gel electrolyte for efficient solid-state supercapacitors - Xu Peng (Nature Portfolio, 2016)
Gel electrolytes are promising for solid-state supercapacitors, due to their favourable properties such as high ion migration rate, mechanical strength, and water retention. Here, the authors report on a zwitterionic gel electrolyte giving robust performance in graphene-based solid-state supercapacitors.